(untitled) (Research, Society and Development, 2020)
Introduction: Dental surgeons routinely deals with third molar extractions in their offices. Then questions about antibiotic prophylaxis in healthy patients start arising. Objective: to verify efficiency of antibiotic prophylaxis during third molar surgery in healthy patients through a literature review. Methods: bibliographic searches were carried out in PUBMED and SCIELO databases. Only case control articles were select, with a range of the last 5 years, resulting in seven articles found at all. Results: Four articles concluded that groups treated without antibiotic prophylaxis obtained the same effects as those who had antibiotics in relation to postoperative infections. One article concluded that antibiotics can be used as antibiotics prophylaxis. Also the achieve that patients who did not have antibiotics are more likely to develop dental alveolitis were concluded in one article. Conclusion: Antibiotic prophylaxis in healthy patients did not present, in most cases, significant results in preventing infections in third molars surgeries. In addition, following the postoperative analgesic and anti-inflammatory medication protocol is sufficient for a good recovery.